Lessons learned from Zaire ebolavirus to help address urgent needs for vaccines against Sudan ebolavirus and Marburg virus - Daniel N. Wolfe; Marva J. Taylor; Amanda G. Zarrabian (Taylor & Francis Group, 2020)
The 2014-2016 Ebola virus epidemic in West Africa triggered extensive investments from public and private partners in an attempt to slow the spread of disease and bring the outbreak under control. This significantly accelerated the pace of development of countermeasures against Zaire ebolavirus that enabled vaccines to be a part of an effective response to the most recent 2018-2019 outbreak in the Democratic Republic of the Congo. However, there remain urgent and unmet needs for medical countermeasures against other members of the Filoviridae family that cause viral hemorrhagic fevers. To improve the national and global preparedness posture for viral hemorrhagic fevers, a renewed emphasis is being placed on developing vaccines for filoviruses other than Zaire ebolavirus. Here we discuss lessons learned from the West Africa epidemic and how those lessons apply to the development of vaccine candidates for other filoviruses, specifically Sudan ebolavirus and Marburg virus. This commentary will highlight some of the key product development gaps to address in preparation for future disease outbreaks caused by these viruses.